1997
DOI: 10.2214/ajr.169.5.9353477
|View full text |Cite
|
Sign up to set email alerts
|

In-phase and out-of-phase MR imaging of bone marrow: prediction of neoplasia based on the detection of coexistent fat and water.

Abstract: OBJECTIVE.The purpose of this study was to determine if gradient-echo MR imagingwith TEs selected with fat and water in phase and out of phase can help predict the likelihood of neoplastic or nonneoplastic lesions in bone marrow. SUBJECTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
130
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(137 citation statements)
references
References 32 publications
6
130
1
Order By: Relevance
“…Further advantages include insensitivity to field inhomogeneities (7) due to paramagnetic substances in bone marrow (18). The opposed-phase technique is based on phase differences of fat and water protons (7,10). Because of the similar fat and water fractions of hematopoietic bone marrow (3), the signal derived from both fractions is canceled by use of an appropriate TE at which the phase shifts are 180°from each other (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further advantages include insensitivity to field inhomogeneities (7) due to paramagnetic substances in bone marrow (18). The opposed-phase technique is based on phase differences of fat and water protons (7,10). Because of the similar fat and water fractions of hematopoietic bone marrow (3), the signal derived from both fractions is canceled by use of an appropriate TE at which the phase shifts are 180°from each other (7).…”
Section: Discussionmentioning
confidence: 99%
“…Seiderer et al (9) showed that the signal in opposed-phase images correlates to the fat/water fraction. Since normal red marrow exhibits low signal in opposed-phase images, pathological processes that result in an increase of water are indicated by high signal (9,10). This sequence proved to be useful in the evaluation of hematopoietic hyperplasia as a result of therapy with granulocyte-colony stimulating factor (G-CSF) in healthy blood stem cell donors at low-field strength (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disler et al [15] studied the relative signal intensity ratios (defined as the ratio of signal intensity of a lesion versus control tissue on opposed-phase imaging divided by the corresponding ratio on in-phase imaging) of lesions in appendicular and pelvic bones. They found that the average relative signal intensity ratio for neoplastic lesions was 1.03, versus 0.61 for non-neoplastic lesions; using a relative signal intensity ratio higher than 0.81 resulted in a sensitivity and specificity of 95% for detection of a tumor.…”
Section: Fat and Water Contentmentioning
confidence: 99%
“…However, water protons process fractionally faster than lipid protons, resulting in a phase difference gradually reaching 1800 in a few milliseconds, which means the phase is opposed, and a refocusing pulse in the GRE sequence can demonstrate the difference between fat and water signal by subtracting them (9 -11). This fat suppression, to some extent, was used to differentiate or reveal the lesions having small amounts of fat and is said to be helpful especially in characterizing the malignant nature of the spinal lesions (9,(11)(12)(13)(14). Now, this technique may gain a newer perspective, establishing an intrinsic value due to its capability to image the spinal structures other than bone marrow, especially the intervertebral disc material, by taking advantage of faster acquisition times in lumbar disc disease.…”
Section: Discussionmentioning
confidence: 99%